Perceptions of Causes, Consequences, and Solutions of Intimate Partner Violence (IPV) in Mexican Women Survivors of IPV: A Qualitative Study - Aniel Jessica Leticia Brambila-Tapia; Ignacio Brambila-Tostado; Martha Patricia Ortega-Medellín; Giovanna Georgina Ramírez-Cerón (Behavioral Sciences)
Intimate partner violence (IPV) is the main cause of violence against women, especially in Mexico. However, the causes, consequences, and solutions related to IPV have not been well understood in this population. A total of five focus groups that included Mexican women who were victims of IPV were conducted to understand the causes, consequences, and solutions related to IPV, and a thematic analysis was performed. A total of 32 participants were included, with a median (range) age of 35 (24–70). The main causes mentioned by the participants were (a) cultural ones, among which Machismo, transgenerational violence, and cultural norms and gender roles were the main categories; (b) emotional causes, among which the lack of emotional abilities and emotional dependence were the main categories; and (c) educative causes, among which the lack of information about mental health, emotional abilities, IPV, and healthy relationships was reported. The main consequences mentioned were (a) psychological; (b) physical; (c) economic; (d) family-related, including impacts on children; and (e) legal, in relation to IPV complaints and children’s custody. Finally, the main solutions mentioned by the participants were (a) prevention through education, including educational programs to address mental health, IPV information, healthy relationships, and training in emotional skills; (b) cultural transformation; and (c) institutional strengthening, with this last solution including improving public policies, improving legal advice, and training for legal authorities. In conclusion, the causes, consequences, and solutions related to IPV were varied and included many instances; therefore, its prevention and solution should be performed at the inter-institutional and community levels, in which the promotion of emotional skills should play a fundamental role.